A randomised controlled trial of tiotropium in adolescents with severe symptomatic asthma. Issue 1 (12th January 2017) - Hamelmann, Eckard; Bernstein, Jonathan A.; Vandewalker, Mark; Moroni-Zentgraf, Petra; Verri, Daniela; Unseld, Anna; Engel, Michael; Boner, Attilio L.
We present results from the first phase III trial of once-daily tiotropium add-on to inhaled corticosteroids (ICS) plus one or more controller therapies in adolescents with severe symptomatic asthma. In this double-blind, parallel-group trial (NCT01277523), 392 patients aged 12–17 years were randomised to receive once-daily tiotropium 5 µg or 2.5 µg, or placebo, as an add-on to ICS plus other controller therapies over 12 weeks. The primary and key secondary end-points were change from baseline (response) in peak forced expiratory volume in 1 s (FEV1 ) within 3 h post-dosing (FEV1(0–3h) ) and trough FEV1, respectively, after 12 weeks of treatment. Tiotropium 5 µg provided numerical improvements in peak FEV1(0–3h) response, compared with placebo (90 mL; p=0.104), and significant improvements were observed with tiotropium 2.5 µg (111 mL; p=0.046). Numerical improvements in trough FEV1 response and asthma control were observed with both tiotropium doses, compared with placebo. The safety and tolerability of tiotropium were comparable with those of placebo. Once-daily tiotropium Respimat add-on to ICS plus one or more controller therapies in adolescents with severe symptomatic asthma was well tolerated. The primary end-point of efficacy was not met, although positive trends for improvements in lung function and asthma control were observed. Tiotropium add-on therapy provided numerical improvements in outcomes in adolescents with asthma http://ow.ly/eL8g304a9XV